Pengaruh Model Problem Based Learning terhadap Pengetahuan Analisis pada Materi Rantai Makanan di Kelas V - Bunga Savira; Azmi Al Bahij (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study is motivated by the difficulty students face in understanding the concept of food chains, which is attributed to the conventional teaching methods still in use. Therefore, the researcher believes that the application of a new teaching model is expected to enhance student engagement in the teaching and learning process, ultimately improving learning outcomes. Natural Science is often considered difficult because of its many theories and the lack of variation in teaching methods, leading to poor student performance. Given these issues, an innovative teaching model is necessary. The aim of this study is to examine the impact of the Problem-Based Learning (PBL) model on students' knowledge in the Natural Science subject. The research method used is an experimental method with a quasi-experimental design. The study population consists of 50 fifth-grade students, with 25 students in the experimental group and 25 students in the control group. The hypothesis tested is that there is an effect of the Problem-Based Learning model on Natural Science learning outcomes. The results of the study show that the Problem-Based Learning model has a significant effect on students' knowledge. This is evidenced by the t-test results, which show a t-value of 12.400, greater than the t-table value of 2.01. Therefore, it can be concluded that the Problem-Based Learning model positively affects the understanding of food chain concepts in fifth-grade students. The findings of this study are expected to be beneficial for teachers in improving the quality of their teaching, for students to better understand the material through more engaging methods, and for the school environment in developing innovative and effective teaching practices.